PELATIHAN PEMBUATAN PANGAN FUNGSIONAL BERBAHAN DASAR PANGAN LOKAL DI DESA SINDANGKARYA KARAWANG - Ratih Kurniasari; Fathma Syahbanu; Pebrianti, Suci Apsari; Zahra, Aliya Azkia; Rahayu, Ikeu Sri; Amalia Khopiyani (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
Metabolic syndrome is a health condition characterized by a collection of medical symptoms consisting of increased waist circumference, increased blood triglyceride levels, decreased blood HDL (high-density lipoprotein) cholesterol levels, high blood pressure, and impaired glucose tolerance. Metabolic syndrome is an early occurrence of degenerative disease. One effort to prevent metabolic syndrome is to increase your intake of food or foodstuffs that have functional benefits. An example of functional food made from local ingredients is instant ginger drink. Ginger is rich in nutrients that inhibit metabolic syndrome and is often found in Sindangkarya Village, Kutaluya District, Karawang Regency, West Java, Indonesia. This activity will focus on increasing participants’ knowledge and skills to make functional food made from local food which has high nutritional value, longer shelf life and is economical so that it can be used as a typical food from Sindangkarya Village to prevent metabolic syndrome. The service activities were carried out in three stages, namely 1) Increasing the knowledge of Sindangkarya Village residents about metabolic syndrome and how to prevent it; 2) Practice making instant ginger as a functional food; 3) Evaluation of activities. The results of service activities include an increase in knowledge and service skills. — Sindrom metabolik merupakan kondisi kesehatan yang ditandai dengan sekumpulan gejala medis yang terdiri atas peningkatan ukuran lingkar pinggang, kadar trigliserida darah yang meningkat, turunnya kadar kolesterol HDL (high density lipoprotein) darah, tekanan darah yang tinggi, serta gangguan toleransi glukosa. Kejadian sindrom metabolic merupakan awal kejadian penyakit degenerratif. Salah satu upaya untuk mencegah terjadinya sindrom metabolik adalah dengan meningkatkan asupan makanan atau bahan pangan yang memiliki manfaat fungsional. Contoh pangan fungsional berbahan lokal adalah minuman jahe instan. Jahe kaya akan zat gizi penghambat sindrom metabolic dan banyak ditemukan di Desa Sindangkarya Kecamatan Kutawaluya, Kabupaten Karawang, Jawa Barat, Indonesia. Kegiatan pengabdian akan berfokus untuk meningkatkan pengetahuan dan keterampilan peserta untuk membuat pangan fungsional berbahan dasar pangan lokal yang memiliki nilai gizi tinggi, daya simpan yang lebih lama, dan ekonomis sehingga dapat dijadikan panganan khas Desa Sindangkarya pencegah sindrom metabolik. Kegiatan pengabdian dilakukan tiga tahap yaitu 1) Peningkatan pengetahuan warga Desa Sindangkarya tentang sindrom metabolik dan cara pencegahannya; 2) Praktek membuat jahe instan sebagai pangan fungsional; 3) Evaluasi kegiatan. Hasil kegiatan pengabdian terjadi peningkatan pengetahuan dan keterampilan peserta pengabdian.